Big Facts and Infographics on Climate Change, Agriculture and Food Security - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Big Facts is a resource of the most up-to-date and robust facts relevant to the nexus of climate change, agriculture and food security. It is intended to provide a credible and reliable platform for fact checking amid the range of claims that appear in reports, advocacy materials and other sources. Full sources are supplied for all facts and figures and all content has gone through a process of peer review.